Vena cava filters in cancer patients: experience with 50 patients Filtros de veia cava inferior em pacientes com câncer: experiência em 50 casos - Antonio Eduardo Zerati; Nelson Wolosker; Guilherme Yazbek; Marcel Langer; Kenji Nishinari (Clinics, 2005)
OBJECTIVE: To study the immediate and late results obtained from the implantation of vena cava filters in cancer patients with deep vein thrombosis concomitant with neoplasia. METHODS: This was a retrospective evaluation of 50 patients with an association of cancer and deep venous thrombosis who underwent interruption of the inferior vena cava and the insertion of permanent vena cava filters. The indications for the procedure, filter implantation technique, early and late complications related to the operation, and the clinical evolution were evaluated. RESULTS: The most frequent indication for filter implantation was the contraindication for full anticoagulant treatment (80%). The femoral vein was the preferred access route (86% of the patients). There were no complications related to the surgical procedure. During the follow-up, the following complications were observed: 1 episode of nonfatal pulmonary thromboembolism, 2 cases of occlusion of the inferior vena cava, and 1 case of thrombus retained in the device. Twenty patients (40%) died due to progression of the neoplasm. CONCLUSIONS: Interruption of the inferior cava vein using an endoluminal filter is a procedure with a low rate of complications. It is a safe and efficient measure for preventing pulmonary embolism in cancer patients who have deep vein thrombosis of the lower limbs. OBJETIVO: Estudar os resultados imediatos e tardios obtidos com a implantação de filtros de veia cava inferior em pacientes com trombose venosa profunda concomitante a neoplasia. MÉTODOS: Avaliamos retrospectivamente 50 pacientes com câncer e trombose venosa profunda associada submetidos a interrupção de veia cava inferior com filtros intraluminais definitivos. Foram estudados aspectos referentes à indicação do procedimento, à técnica de implante dos dispositivos, complicações precoces e tardias relacionadas à operação e à evolução dos pacientes. RESULTADOS: A indicação mais freqüente para o procedimento foi a impossibilidade de anticoagulação plena (80% ) e a via de acesso preferencial foi a punção da veia femoral, realizada em 86% dos pacientes. Não houve complicações relativas ao implante dos filtros. Durante a evolução ocorreram: um episódio de tromboembolia pulmonar não fatal e dois casos de oclusão da veia cava inferior; em um paciente foi demonstrada a presença de coágulo retido no dispositivo. Vinte pacientes (40%) faleceram devido à neoplasia. CONCLUSÃO: A interrupção da veia cava inferior com filtro endoluminal é um procedimento com baixo índice de complicações e eficaz na prevenção da embolia pulmonar nos pacientes com tromobose venosa profunda de membros inferiores portadores de câncer.